Addison [compact disc] - Rae, Addison, 2000-; Anderfjärd, Elvira; Klosner, Luka; Burman, Tove (Columbia Records, 2025)
"Addison Rae's debut album will be released on June 6th, 2025, via Columbia Records. The album features previous hits "Diet Pepsi," "Aquamarine," and "High Fashion," plus the recently released "Headphones On." It features twelve tracks and was written and produced by Addison, Luka Kloser and Elvira Anderfjärd." --www.cvsmidwesttape.ca.